1039 Time course of left atrial performance in patients with paroxysmal atrial fibrillation undergoing radio-frequency catheter isolation of pulmonary veins. (17th January 2020) - Katbeh, A; Iliodromitis, K; De Potter, T; Geelen, P; Balogh, Z; Stefanidis, E; Barbato, E; Van Camp, G; Penicka, M
Abstract: Background: Radio-frequency catheter isolation of pulmonary veins (RF-PVI) is associated with changes of left atrial (LA) structure and function. However, there is limited knowledge regarding the long-term impact of successful RF-PVI on the LA mechanics. The aim of the current study was to assess the time course of LA performance in patients with paroxysmal atrial fibrillation (pAF) undergoing RF-PVI. Methods: The study population included 24 consecutive patients (age:62 ± 21 years; 66% male) with symptomatic pAF and preserved left ventricular ejection fraction (≥50%) undergoing the first RF-PVI and 23 healthy controls. A comprehensive echocardiographic examination was performed one day before and 1 day, 3- and 12- months after RF-PVI. The reservoir, conduit and contractile LA strain (LAS), strain rate (LASR) and mechanical dispersion (LAMD) were assessed using two-dimensional speckle tracking echocardiography in apical views. Results: At baseline, patients with pAF showed a significant reduction of all three components of LAS and LASR compared with controls (all p < 0.01). At 1 day after RF-PVI, LAS and LASR showed significant decrease compared with baseline (all p < 0.05) (figure). At 3-month follow up, LAS and LASR recovered to baseline values while LAMD showed a significant improvement (77ms vs 58ms, p = 0.003). At 12-month follow up, both reservoir and contractile LAS showed further improvement compared to 3-month values (31% vs 27%, and 15% vs 13%, both p < 0.05). Yet, even after 12 months, LAS values remained significantly lower compared with healthy controls (p < 0.05). LA emptying fraction was restored and LA end-systolic (max) and end-diastolic (min) volume index showed a significant decrease compared to baseline and 3-month values (all p < 0.05). Conclusion: Successful RF-PVI is associated with acute decrease in LAS, followed by recovery to baseline values within 3 months and further improvement during one year. Reservoir and contractile LAS appears to be the most clinically useful indices to monitor LA performance in patients with pAF undergoing RF-PVI. Figure: Time course of LA reservoir and contractile strain, LA max and min volume index, and LA mechanical dispersion (Baseline, 1-day FUP, 3- and 12-month FUP).